"Emplotted Narratives" and Structured "Behavioral Observations" Supporting the Diagnosis of Willis‐Ekbom Disease/Restless Legs Syndrome in Children with Neurodevelopmental Conditions. (13th June 2016) - Ipsiroglu, Osman S.; Beyzaei, Nadia; Berger, Mai; Wagner, Alexandra L.; Dhalla, Sophia; Garden, Jennifer; Stockler, Sylvia
Summary: Background: Willis‐Ekbom disease/restless legs syndrome (WED/RLS) seems to be a frequent cause of intractable chronic insomnia (ICI) but is under‐recognized in children/adolescents with neurodevelopmental conditions (NDCs), as many patients do not have the ability to express the underlying "urge‐to‐move". In light of this, we aim to develop a protocol for behavioral observations supporting the diagnosis of WED/RLS. Methods: We investigated 26 pediatric patients (age 1–16 years, median 8) with NDCs, ICI and evidence of familial WED/RLS employing (1) "emplotted narratives" for description of the various "urge‐to‐move" presentations and (2) self‐description and "behavioral observations" during a "suggested clinical immobilization test" (SCIT). Results: Parental narratives reflected typical WED/RLS‐related "urge‐to‐move" symptoms during day‐, bed‐, and nighttime in all patients. Fifteen out of 26 patients could describe the "urge‐to‐move" during the SCIT. Ten out of 26 patients, unable to describe their symptoms due to cognitive disabilities, showed patterns of "relieving‐movements" upon observation. Sensory processing abnormalities were reported in all patients, with tactile sensitivities (26/26) (including shifted pain threshold) as the most common sensory domain. Conclusion: "Emplotted narratives" and structured "behavioral observations" support recognition of familial WED/RLS associated movement patterns and provide a useful tool for the diagnosis of WED/RLS in children with NDCs in a clinical office setting.